7-Deoxy-13-dihydrodaunomycinone in cultures of Streptomyces coeruleorubidus - Matĕjů, J; Vokoun, J; Blumauerová, M; Vanĕk, Z (Folia microbiologica, 1978)
7-Deoxy-13-dihydrodaunomycinone was isolated from three strains of Streptomyces coeruleorubidus. Its production was found to rise at the end of cultivation and to be stimulated by lowered aeration intensity.
Keywords: Daunorubicin; Streptomyces; daunomycin